If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + 3(-6x + -16) = 18 Reorder the terms: -4x + 3(-16 + -6x) = 18 -4x + (-16 * 3 + -6x * 3) = 18 -4x + (-48 + -18x) = 18 Reorder the terms: -48 + -4x + -18x = 18 Combine like terms: -4x + -18x = -22x -48 + -22x = 18 Solving -48 + -22x = 18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '48' to each side of the equation. -48 + 48 + -22x = 18 + 48 Combine like terms: -48 + 48 = 0 0 + -22x = 18 + 48 -22x = 18 + 48 Combine like terms: 18 + 48 = 66 -22x = 66 Divide each side by '-22'. x = -3 Simplifying x = -3
| V=1R | | 14bg-5bg-8bg= | | 2x=(x-2)+4 | | log(x+5)13=1 | | V=1timesr | | 19=-x-9 | | 6x-21=87 | | 15x+35=8x-70 | | 21x+70=-140 | | 125^3b=1/25 | | 20-3w=10+4w | | 8a-6=3a+4 | | 20=h-1 | | -4(-6w+v)-6(-6v+w)= | | -1(-8.3+2.3)= | | V=1xRanswer | | 3f+3=-13 | | -10=-2+1d | | 7-1.7=28.5 | | -4/9=2/9n-2/5 | | 0.4(3.2x+2)-x=2z+1.8 | | 12m=3.96 | | -2(4+2x)=-8+x | | y-5.5=12 | | y+3.4=15 | | 5(4-3x)=4(4-3x) | | 3b+3(3b+2)=-42 | | 5(x+8)-9=9 | | 4/3x3.14x3 | | 4/3x3.14x3cubed | | 32(x-1)+114x+5(x+3)=1607 | | 8-y=11-8 |